New Insights on Drought Stress Response by Global Investigation of Gene Expression Changes in Sheepgrass (Leymus chinensis) - Zhao, Pincang (Front Plant Sci, 2016)
Water is a critical environmental factor that restricts the geographic distribution of plants. Sheepgrass [Leymus chinensis, (Trin.) Tzvel] is an important forage grass in the Eurasia Steppe and a close germplasm for wheat and barley. This native grass adapts well to adverse environments such as cold, salinity, alkalinity and drought, and it can survive when the soil moisture may be less than 6% in dry seasons. However, little is known about how sheepgrass tolerates water stress at the molecular level. Here, drought stress experiment and RNA-sequencing (RNA-seq) was performed in three pools of RNA samples (control, drought stress, and rewatering). We found that sheepgrass seedlings could still survive when the soil water content (SWC) was reduced to 14.09%. Differentially expressed genes (DEGs) analysis showed that 7320 genes exhibited significant responses to drought stress. Of these DEGs, 2671 presented opposite expression trends before and after rewatering. Furthermore, ~680 putative sheepgrass-specific water responsive genes were revealed that can be studied deeply. Gene ontology (GO) annotation revealed that stress-associated genes were activated extensively by drought treatment. Interestingly, cold stress-related genes were up-regulated greatly after drought stress. The DEGs of MAPK and calcium signal pathways, plant hormone ABA, jasmonate, ethylene, brassinosteroid signal pathways, cold response CBF pathway participated coordinatively in sheepgrass drought stress response. In addition, we identified 288 putative transcription factors (TFs) involved in drought response, among them, the WRKY, NAC, AP2/ERF, bHLH, bZIP, and MYB families were enriched, and might play crucial and significant roles in drought stress response of sheepgrass. Our research provided new and valuable information for understanding the mechanism of drought tolerance in sheepgrass. Moreover, the identification of genes involved in drought response can facilitate the genetic improvement of crops by molecular breeding.